Histone 3 Lysine 9 Trimethylation Is Differentially Associated with Isocitrate Dehydrogenase Mutations in Oligodendrogliomas and High-Grade Astrocytomas - Venneti, Sriram (2013)
Trimethylation of histone 3 lysine 9 (H3K9me3) is a marker of repressed transcription. Cells transfected with mutant isocitrate dehydrogenase (IDH) show increased methylation of histone lysine residues, including H3K9me3, due to inhibition of histone demethylases by 2-hydroxyglutarate. Here, we evaluated H3K9me3 and its association with IDH mutations in 284 gliomas. H3K9me3 was significantly associated with IDH mutations in oligodendrogliomas. Moreover, 72% of World Health Organization grade II and 65% of grade III oligodendrogliomas showed combined H3K9me3 positivity and 1p19q co-deletion. In astrocytic tumors, H3K9me3 positivity was found in all grades of tumors; it showed a significant relationship with IDH mutational status in grade II astrocytomas but not in grade III astrocytomas or glioblastomas. Finally, H3K9me3-positive grade II oligodendrogliomas but not other tumor subtypes showed improved overall survival compared to H3K9me3-negative cases. These results suggest that repressive trimethylation of H3K9 in gliomas may occur in a context-dependent manner and is associated with IDH mutations in oligodendrogliomas, but may be differently regulated in high-grade astrocytic tumors. Further, H3K9me3 may define a subset of grade II oligodendrogliomas with better overall survival. Our results suggest variable roles for IDH mutations in the pathogenesis of oligodendrogliomas vs. astrocytic tumors.